2023
DOI: 10.5343/bms.2022.0059
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Marine Debris in the Florida Keys Coral Reef Ecosystem by Nonindigenous Sun Corals (Tubastraea Spp.)

Abstract: Indo-Pacific sun corals (Tubastraea spp.) are aggressive competitors capable of disrupting the structure and function of natural reef habitat in the western Atlantic. Sun corals observed on rope debris entangled on an artificial reef in the Florida Keys suggest a potential dispersal mechanism for the colonization of natural reef habitat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…For instance, the oviposition of fishes on marine debris was not noted in this study but has been raised as an area needing further research by Shruti et al (2023). Additionally, we note that non-indigenous species such as sun corals, Tubastrea spp., which have been previously documented on marine debris in the Florida Keys (Parsons et al, 2023) were not identified in this study and require further investigation to determine the cost and benefits of debris materials as substrate or refuge.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, the oviposition of fishes on marine debris was not noted in this study but has been raised as an area needing further research by Shruti et al (2023). Additionally, we note that non-indigenous species such as sun corals, Tubastrea spp., which have been previously documented on marine debris in the Florida Keys (Parsons et al, 2023) were not identified in this study and require further investigation to determine the cost and benefits of debris materials as substrate or refuge.…”
Section: Discussionmentioning
confidence: 98%